Black Hole and Neutron Star Binary Mergers in Triple Systems. II. Merger Eccentricity and Spin-Orbit Misalignment - Liu, Bin; Lai, Dong; Wang, Yi-Han (The Astrophysical journal, 2019)
We study the dynamical signatures of black hole (BH) and neutron star (NS) binary mergers via Lidov-Kozai oscillations induced by tertiary companions in hierarchical triple systems. For each type of binary (BH-BH and BH-NS), we explore a wide range of binary/triple parameters that lead to binary mergers and determine the distributions of merger time Tm, eccentricity (em), and spin-orbit misalignment angle ( ) when the binary enters the LIGO/VIRGO band (10 Hz). We use the double-averaged (over both orbits) and single-averaged (over the inner orbit) secular equations, as well as N-body integration, to evolve systems with different hierarchy levels, including the leading-order post-Newtonian effect, de Sitter spin-orbit coupling, and gravitational radiation. We find that for merging BH-BH binaries with comparable masses, about 7% have em > 0.1 and 0.7% have em > 0.9. The majority of the mergers have significant eccentricities in the LISA band. The BH spin evolution and the final spin-orbit misalignment are correlated with the orbital evolution and em. Mergers with negligible em ( 10−3) have a distribution of that peaks around 90° (and thus favoring a projected binary spin parameter χeff ∼ 0), while mergers with larger em have more isotropic spin-orbit misalignments. For typical BH-NS binaries, strong octupole effects lead to more mergers with nonnegligible em (with ∼18% of the mergers having em > 0.1 and 2.5% having em > 0.9), and the final BH spin axis tends to be randomly oriented. Measurements or constraints on eccentric mergers and from LIGO/VIRGO and LISA would provide useful diagnostics on the dynamical formation of merging BH or NS binaries in triples. The recently detected BH merger events may implicate such dynamical formation channel.